Antioxidative Potential of Consciousness Energy Healing Treatment on HepG2 Cells and DMEM after Oxidative Stress Induced by Hydrogen Peroxide - Kumar Trivedi, Mahendra; Branton, Alice; Trivedi, Dahryn; Nayak, Gopal; Charan Mondal, Sambhu; Jana, Snehasis (Journal of Antioxidant Activity, 2018)
Antioxidants can reduce oxidative stress in cells is used for the treatment of several disorders such as cancer, cardiovascular, and inflammatory diseases. The present study was evaluated the antioxidant potential of the Consciousness Energy Healing (The Trivedi Effect®) Treated human hepatoma cell line (HepG2) and Dulbecco's Modified Eagle Medium (DMEM) for the assessment of cell viability under hydrogen peroxide-induced oxidative stress. The Biofield Energy Treated HepG2 cells group was maintained for 23 days under standard conditions. On the next day, the cells were challenged with 1 mM of H2O2 for the generation of oxidative stress. The ability of the Biofield Energy Healing Treatment to protect from the oxidative stress was determined by MTT cell viability assay and compared with the negative control group. The percentage of cell viability was significantly (p≤0.001) increased by 13.6% in the Biofield Energy Treated DMEM group; while altered by 3.2% in the Biofield Energy Treated HepG2 cells group compared to the negative control groussp. Overall, the Biofield Energy Treated DMEM showed a better antioxidative protection against oxidative stress than HepG2 cells group, which was induced by H2O2. Therefore, the results envisaged that The Trivedi Effect®- Biofield Energy Healing Treatment has an impact on the protection of various vital organs from oxidative stress; which might be helpful in the development of powerful/energized growth medium for the accelerated study with a cost-effective manner.
Keywords: Antioxidant; Consciousness Energy Healing; The Trivedi Effect; HepG2; Oxidative Stress